MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA MELALUI PEMBELAJARAN MODEL TREFFINGER - Bambang Priyo Darminto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
One of the professional competences of mathematics teacher is the ability of mathematical problem solving. At high school level, the increase of this ability is influenced by creativity. It means, that if the students’ creativity is getting higher, their ability of mathematical problem solving is also progressively better, conversely. The applying of  Treffinger’s model in mathematics teaching and learning at high school, have been proven can develop the students’ creativity. In this research, Treffinger’s model is applied to  students prepared for being mathematics teacher as a mean to improve their ability of  mathematical problem solving. The sampels consist of 32 students of Mathematics Educational Department, taken by purposive sampling. The data collecting uses instrument in the form of test about the ability of mathematical problem solving. The result of this research indicates that the applying of  Treffinger’s model is significant influencing the increase of the mathematical problem solving’s ability. It is caused by the fact that the students have their own variation, creativity, and experience so that can be developed swiftly in mathematical problem solving.